Peranan Willem Iskandar (Sati Nasution) dalam Perkembangan Pendidikan di Sumatera Utara - Hasibuan, Yunita Syari Denny (Islamic Education, 2024)
This research discusses the role of Willem Iskandar (Sati Nasution) in the development of education in North Sumatra in the 19th century. Willem Iskandar is known as a visionary educator who founded Kweekschool Tano Bato, the first educational institution for teachers in Mandailing in 1862. With the support of the Dutch authorities and the local community, he played a crucial role in establishing a strong educational foundation in the region. Besides being an educator, Willem Iskandar was also active as a translator, bringing Western literature to the Mandailing community through translations of important works and original writings in Mandailing and Malay languages. His intellectual legacy not only enriched the intellectual life of the Mandailing community at that time but also demonstrated his significant role in the history of education in North Sumatra. This study employs historical approaches and literary analysis to explain the impact of his contributions to the development of education and literacy in the region. Thus, this research provides a comprehensive overview of Willem Iskandar's role in advancing education in North Sumatra in the 19th century.